2006
DOI: 10.1007/s00213-006-0413-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors influencing medication compliance in inpatient treatment of psychotic disorders

Abstract: Patient-related in addition to disease-related factors may strongly influence medication compliance. Besides more compliance with atypicals supposed by the literature, there may be a higher propensity for atypical drugs to be prescribed to those assumed to be more compliant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
4

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 25 publications
(22 reference statements)
3
75
0
4
Order By: Relevance
“…Literature showed one of the commonest reason cited for discontinuation of medication was poor financial status. 10 But the other study showed in-spite of the…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Literature showed one of the commonest reason cited for discontinuation of medication was poor financial status. 10 But the other study showed in-spite of the…”
Section: Resultsmentioning
confidence: 90%
“…denial of illness & side effect of medications. 9 Study conducted by Janssen B et al reported that individual who switched from a typical to an atypical antipsychotic drug more compliant was observed; it may be due to lesser side effects 10 .They also revealed that perceived benefit from medication proved to be the main reason for patients compliance with neuroleptic treatment. With regards to association between level of compliance and treatment access related factors, significant association was found (P<0.05).…”
Section: Lama S Et Al May-august 2012; Vol 10 (No2);113-117mentioning
confidence: 98%
“…The evidence suggests that sociodemographic factors such as gender [Acosta et al 2009;Linden et al 2001] and family/marital status [Acosta et al 2009;Linden et al 2001] do not influence adherence as the association between nonadherence and these variables were not significant in most studies. However, results were mixed concerning ethnicity [Aldebot and de Mamani, 2009;Valenstein et al 2004], level of education [Acosta et al 2009;Aldebot and de Mamani, 2009;Hudson et al 2004;Janssen et al 2006;Linden et al 2001;Loffler et al 2003] and age [Acosta et al 2009;Linden et al 2001;Valenstein et al 2004]. Lack of insight was significantly associated with nonadherence in all studies [Acosta et al 2009;Aldebot and de Mamani 2009;Loffler et al 2003;Olfson et al 2006] except one [Linden et al 2001].…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving the conventional antipsychotics had earlier implicated the incidence of akathisia as a major determinant of treatment discontinuation. 17,46 However, with the increased use of the second-generation, atypical antipsychotics, akathisia has become less of an issue, 9,47 and indeed current thinking is that lack of efficacy, rather than tolerability profile, is a stronger predictor of early discontinuation. 7,35,[48][49][50] Medication noncompliance and undercompliance continue to be a problem in the treatment of schizophrenia; the vast majority of hospital admissions for exacerbation of psychosis have been linked to noncompliance, 6,51 which may still be the most important militating factor in relapse.…”
Section: Discussionmentioning
confidence: 99%